2011
DOI: 10.1007/s11274-011-0747-x
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles using Rhodobacter Sphaeroides

Abstract: The use of microorganisms in the synthesis of nanoparticles emerges as an eco-friendly and exciting approach. In this study, silver nanoparticles were successfully synthesized from AgNO 3 by reduction of aqueous Ag ? ions with the cell filtrate of Rhodobacter sphaeroides. Nanoparticles were characterized by means of UV-vis absorption spectroscopy, X-Ray Diffraction (XRD), transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM). Crystalline nature of the nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 28 publications
3
22
0
1
Order By: Relevance
“…The present results showed that temperature had an appreciable effect on the synthesis rate and the size of AgNPs. Similar results were demonstrated by Bai et al (2011) and Jeevan et al (2012) using Rhodobacter sphaeroides and Pseudomonas aeruginosa, respectively, and the optimum temperature for AgNP synthesis was found to be 35 °C. Two other reports indicated that E. coli (Gurunathan et al, 2009) and Bacillus subtilis EWP-46 (Velmurugan et al, 2014) required a higher temperature (60 °C) to synthesize AgNPs.…”
Section: Discussionsupporting
confidence: 88%
“…The present results showed that temperature had an appreciable effect on the synthesis rate and the size of AgNPs. Similar results were demonstrated by Bai et al (2011) and Jeevan et al (2012) using Rhodobacter sphaeroides and Pseudomonas aeruginosa, respectively, and the optimum temperature for AgNP synthesis was found to be 35 °C. Two other reports indicated that E. coli (Gurunathan et al, 2009) and Bacillus subtilis EWP-46 (Velmurugan et al, 2014) required a higher temperature (60 °C) to synthesize AgNPs.…”
Section: Discussionsupporting
confidence: 88%
“…compared to A. fumigatus and this may be due to the fact that the faster growing Streptomyces may produce higher concentrations and different reductase enzymes than the A. fumigatus fungus. The role of NADH dependent nitrate reductase from fungi in the biosynthesis of silver nanoparticles was recently reported (Kumar et al 2007, Bai et al 2011). However, different NADH-dependent reductases may be produced also by Streptomyces sp.…”
Section: Resultsmentioning
confidence: 95%
“…It was found that cotton fabrics incorporated with silver nanoparticles displayed a significant antibacterial activity (Durán et al 2007). Recently, silver nanoparticles have been biosynthesized by a variety of microorganisms such as cyanobacteria (Lengke et al 2007), photosynthetic bacteria (Bai et al 2011) and fungi (Chen et al 2003;Vigneshwaran et al 2007;Basavaraja et al 2008). The biosynthesis of nanoparticles is affected by the species and even the strain of the microorganism as it is highly dependent upon the enzymes or other components produced by the cell that reduce AgNO 3 to Ag 0 , as well as the organism's tolerance to higher AgNO 3 concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…It is also evident that the increased antimicrobial activity of AgNPs may be attributed to its special characteristics of small size and high surface area to volume ratio [19]. The advantage of adapting biosynthesis of AgNPs is the simplicity of extracellular synthesis and downstream processing [20, 21]. …”
Section: Introductionmentioning
confidence: 99%